Pengaruh Brand trust dan Perceived Ease of Use terhadap Repurchase Intention melalui Customer satisfaction sebagai Variabel Intervening pada Konsumen Pengguna Traveloka - Ahmad Irfan Pramudia; Nurul Komaryatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of brand trust and perceived ease of use on repurchase intention through customer satisfaction as an intervening variable among Traveloka users. This research employs a quantitative approach using Structural Equation Modeling (SEM) and involves 154 respondents selected through purposive sampling, with data collected Likert-scale questionnaires. The results indicate that brand trust has a positive and significant effect on both repurchase intention and customer satisfaction, and perceived ease of use also has a positive and significant effect on both repurchase intention and customer satisfaction. However, customer satisfaction does not have a significant effect on repurchase intention, and also indicating that it does not act as an intervening variable in this research. These findings suggest that consumers repurchase intention is more directly influenced by brand trust and ease of use rather than being mediated by customer satisfaction, implying that companies should focus on strengthening brand trust and enhancing user experience to maintain customer loyalty.